Alteration of AKT Activity Increases Chemotherapeutic Drug and Hormonal Resistance in Breast Cancer yet Confers an Achilles Heel by Sensitization to Targeted Therapy - McCubrey, James A.; Sokolosky, Melissa L.; Lehmann, Brian D.; Taylor, Jackson R.; Navolanic, Patrick M.; Chappell, William H.; Abrams, Stephen L.; Stadelman, Kristin M.; Wong, Ellis WT; Misaghian, Negin; Horn, Stefan; Basecke, Jorg; et al. (East Carolina University, 2008)
The PI3K/PTEN/Akt/mTOR pathway plays critical roles in the regulation of cell growth. The effects of this pathway on drug resistance and cellular senescence of breast cancer cells has been a focus of our laboratory. Introduction of activated Akt or mutant PTEN constructs which lack lipid phosphatase [PTEN(G129E)] or lipid and protein phosphatase [PTEN(C124S)] activity increased the resistance of the cells to the chemotherapeutic drug doxorubicin, and the hormonal drug tamoxifen. Activated Akt and PTEN genes also inhibited the induction of senescence after doxorubicin treatment; a phenomenon associated with unrestrained proliferation and tumorigenesis. Interference with the lipid phosphatase domain of PTEN was sufficient to activate Akt/mTOR/p70S6K as MCF-7 cells transfected with the mutant PTEN gene lacking the lipid phosphatase activity [PTEN(G129E)] displayed elevated levels of activated Akt and p70S6K compared to empty vector transfected cells. Cells transfected with mutant PTEN or Akt constructs were hypersensitive to mTOR inhibitors when compared with the parental or empty vector transfected cells. Akt-transfected cells were cultured for over two months in tamoxifen from which tamoxifen and doxorubicin resistant cells were isolated that were >10-fold more resistant to tamoxifen and doxorubicin than the original Akt-transfected cells. These cells had a decreased induction of both activated p53 and total p21Cip1 upon doxorubicin treatment. Furthermore, these cells had an increased inactivation of GSK-3β and decreased expression of the estrogen receptor-α. In these drug resistant cells, there was an increased activation of ERK which is associated with proliferation. These drug resistant cells were hypersensitive to mTOR inhibitors and also sensitive to MEK inhibitors, indicating that the enhanced p70S6K and ERK expression was relevant to their drug and hormonal resistance. Given that Akt is overexpressed in greater than 50% of breast cancers, our results point to potential therapeutic targets, mTOR and MEK. These studies indicate that activation of the Akt kinase or disruption of the normal activity of the PTEN phosphatase can have dramatic effects on activity of p70S6K and other downstream substrates and thereby altering the therapeutic sensitivity of breast cancer cells. The effects of doxorubicin and tamoxifen on induction of the Raf/MEK/ERK and PI3K/Akt survival pathways were examined in unmodified MCF-7 breast cells. Doxorubicin was a potent inducer of activated ERK and to a lesser extent Akt. Tamoxifen also induced ERK. Thus a consequence of doxorubicin and tamoxifen therapy of breast cancer is the induction of a pro-survival pathway which may contribute to the development of drug resistance. Unmodified MCF-7 cells were also sensitive to MEK and mTOR inhibitors which synergized with both tamoxifen and doxorubicin to induce death. In summary, our results point to the key interactions between the PI3K/PTEN/Akt/mTOR and Raf/ MEK/ERK pathways in regulating chemotherapeutic drug resistance/sensitivity in breast cancer and indicate that targeting these pathways may prevent drug and hormonal resistance. Orignally published Advances in Enzyme Regulation, Vol. 48, No. 1, 2008.
Keywords: Conventional therapy; Targeted therapy; Signal transduction inhibitors; Breast--Cancer